(3GSJNOGeGJ GdaVGA GdNGQLj (B: s (3OQGSI aj GdbGfhf GdOhdj deOi TQYjI GSJNOGeGJ GdOhd ddaVGA GdNGQLj (B/ s - (3fOi Yd`j YH`OGddWja GdCfU`GQj s; (3CMe`O CH`hGdha`G (B: s ((3GdbGgQI (B: s (3fOi Yd`j YH`OGddWja GdCfU`GQj (B: s, 2014)
(3jYO GdaVGA GdNGQLj ejOGfkG LOjOkG dCfTWI GdOhd HMceI bGfhf GdaVGA hgh bGfhf MOjK GdJchjf(B: (3hdG jRGd jThHg GdcKjQ ef GdZehV hHGdJGdj GddHS aj GdJWHjb(B. (3hJbSe GSJNOGeGJ GdOhd ddaVGA GdNGQLj Edi GSJNOGeGJ SdejI hCNQi ZjQ SdjeI(B: (3hbO GMJOe LOd TOjO Mhd JaSjQ eUWdM GdGSJNOGe GdSdej hSHH gPG GdLOd jQLY Edi eUGdM GdOhd GdeJbOeI hYdi QCSgG GdhdGjGJ GdeJMOI (B: (3EdG Cf GdGSJNOGe GdSdej habkG ddefWb GdbGfhfj hGdabg gh GdGSJNOGe GdeOfj hGdYdej hGdGSJNOGe ZjQ GdSdej gh GdGSJNOGe GdYScQj hGdJLSS(B. (3jbSe GSJNOGe GdaVGA GdNGQLj Edi GSJNOGeGJ SdejI hCNQi ZjQ SdejI bO Jchf YScQjI Ch CYeGd JLSS hdGHO ef JfXje gPg GdGSJNOGeGJ HeYGgOI OhdjI LOjOI hGVMI dG dHS aj ehGOgG s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdOhdi GdYGes
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdaVGA GdNGQLjs; (3GdbGfhf GdOhdj s; (3TQYjI GSJNOGeGJ GdOhd ddaVGA GdNGQLj s